2023
DOI: 10.3390/cancers15102713
|View full text |Cite
|
Sign up to set email alerts
|

The Black Hole: CAR T Cell Therapy in AML

Abstract: Despite exhaustive studies, researchers have made little progress in the field of adoptive cellular therapies for relapsed/refractory acute myeloid leukemia (AML), unlike the notable uptake for B cell malignancies. Various single antigen-targeting chimeric antigen receptor (CAR) T cell Phase I trials have been established worldwide and have recruited approximately 100 patients. The high heterogeneity at the genetic and molecular levels within and between AML patients resembles a black hole: a great gravitation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 148 publications
0
8
0
Order By: Relevance
“… 46 , 47 The results of existing clinical studies have shown that although CAR-T cells targeting CD33, CD123, and CLL-1 have certain curative effects, they face problems such as poor persistence, insufficient efficacy, and target escape. 48 , 49 Dual-targeted CAR-T cells have been found in studies to have more activity and affinity for tumor cells than single-targeted CART cells, and more importantly, dual-targeted CART cells control disease more consistently. 50–53 CD123 and NKG2DLs are good CAR targets as they are known to be elevated in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 The results of existing clinical studies have shown that although CAR-T cells targeting CD33, CD123, and CLL-1 have certain curative effects, they face problems such as poor persistence, insufficient efficacy, and target escape. 48 , 49 Dual-targeted CAR-T cells have been found in studies to have more activity and affinity for tumor cells than single-targeted CART cells, and more importantly, dual-targeted CART cells control disease more consistently. 50–53 CD123 and NKG2DLs are good CAR targets as they are known to be elevated in AML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite disappointing progress in the field of immunotherapeutic approaches in AML ( 197 ), the implementation of proteomics ( 198 ) and transcriptomics ( 199 ) in designing a more personalized CAR-T-cell therapies holds promises. Single-cell sequencing offers the possibility to investigate mutational changes across the DNA, epigenetic and protein level ( 200 ). A recent review by Shahzad et al.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, AML is a very heterogeneous disease and varies between patients depending on chromosomal abnormalities and mutations. It also creates a very immunosuppressive tumor microenvironment containing various cell types like regulatory T cells, macrophages, dendritic cells, and myeloid-derived suppressor cells that suppress T-cell activity and decrease CAR T-cell responses [46]. Addressing this concern, a current approach under investigation involves the use of CRISPR/Cas9 technology to edit out the CAR target antigen from a donor allograft.…”
Section: Investigational Therapiesmentioning
confidence: 99%